Pedagogical practice for the development of creativity and innovation in second grade of primary basic - Ávila Pallares, Lady Yuley (Universidad Francisco de Paula Santander, 2017)
This mixed type investigation enquired the pedagogical practices of teachers for the development ofcreativity and innovation in the second grade of the Municipal School Educational Institution Airport of the city ofCúcuta. For this, he used the Theory of Sociocultural Creativity defined by Dr. De Prado (2011); The methodologicalprocedure that allowed to inquire about these practices was supported by two techniques of getting data such as thequestionnaire and the focus group, this first carried out to the 5 teachers and the focus group to 10 students, two of each second grade course.The study was divided into 4 dimensions: Dimension 1. Educational Environment, Dimension 2, Interaction with thestudent, Dimension 3. Methodology and Dimension 4. Learning, in which you will see weaknesses regarding to the pedagogical practices of teachers and their interest in the development of creativity and innovation in their students.